The influence of a Pandemic on Decision Making - Jarrett, Jeffrey (Advances in Social Sciences Research Journal, 2022)
A Discussion of Capital budgeting models will be discussed in this manuscript to bring forth the notion that present value of cash flows is often improperly estimated. Financial models utilized in the decision analytic process. In particular, intellectual property rights and other intangible assets often are often not considered in accounting estimation processes utilized in financial accounting (Jarrett, 2021). A decision maker often utilizes misestimates of the present value of cash flow resulting in less-than-optimum capital budgeting decisions. Decisions to abandon for salvage, sale and other disposal methods improve when the present value of intangibles and property rights are included in the decision process. In particular, this last statement improves the estimation process in financial accounting, finance and abandonment and decision theoretic decisions in capital budgeting which are well-founded results in abandonment of property in both intellectual f this study as well as to present well-founded processes to improve abandonment in capital budgeting decisions involving cost estimation, matching of costs and revenues and equivalent problems in the recognition revenues with costs in financial decision processes.